HIV Associated Neurocognitive Disorders Subsidence Through Citalopram Addition in Anti-retroviral Therapy (HANDS-CARE): A Concept Note - Ojagbemi, Akin (Frontiers in Neurology, 2021)
There is a pressing need to effectively manage HIV Associated Neurocognitive Disorders (HAND) in sub-Saharan Africa (SSA) where the burden is among the highest in the world. Contemporary approaches based on the use of Highly Active Antiretroviral Therapy (HAART) alone are inadequate interventions for HAND, especially in SSA where there is limited availability of the required combinations of HAART for effective central nervous system penetration and where many currently prescribed agents, including efavirenz, have neurotoxicity as a major drawback. This article reviews data supporting the rationale for additive citalopram in antiretroviral therapy as a latent approach to abate HAND, and propose the conduct of a HIV Associated Neurocognitive Disorders Subsidence through Citalopram Addition in antiretroviral therapy (HANDS-CARE) pilot Randomized Controlled Trial (RCT) to assess whether the adjunctive use of citalopram, a widely prescribed serotonergic antidepressant, will lead to a meaningful improvement in neurocognitive functioning and quality of life in patients with HAND who are receiving HAART. A preliminarily feasible and efficacy-suggesting HANDS-CARE trial could generate statistical, clinical and operational data necessary to design and conduct a future definitive multicenter RCT. If successful, this intervention will be applicable to resource-limited settings as well as developed countries. Effective management of HAND will improve the quality of life of HIV patients, and reduce the cost of managing the disease.